Creation of Standard DNA for Detection and Quantification of White Spot Syndrome Virus in Shrimps by Real-time PCR (qPCR) - Cuong, Tran Viet; Nghia, Phan Tuan; Loan, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology, 2022)
White spot syndrome virus (WSSV) is a double stranded DNA virus that causes WSS diseases for many crustaceans including the Penaeidae family shrimp. In this study, standard DNA for detection and quantification of WSSV by real-time polymerase chain reaction (qPCR) method was created. A specific gene fragment of 126 bp from WSSV genome was successfully amplified by PCR and cloned into pGEM-T vector. qPCR calibration curves using the created recombinant pGEM vector harboring 126 bp gene fragment as the standard DNA at concentrations of 3x10 2 to 3x10 8 copies/mL showed to have good linear regression with an efficiency of 99.1%, correlation coefficient R 2 of 0.998 and the slope of -3.344. The recombinant vector was also used as a positive standard for detection and quantification of WSSV in a number of WSSV-infected shrimp samples and the values ranging from 3.69x10 3 copies/mL to 1.25x10 8 copies/mL WSSV were found in the collected samples.